Introduction - Images, Redakcja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This issue of “Images” is entitled Ukraine in Flames, echoing the English-language adaptation of a renowned cinematic creation byUkrainian director Oleksandr Dovzhenko (1894–1956). In 1944, Stalin’s regime condemned this masterpiece to oblivion, citing unfounded al- legations of “Ukrainian nationalism”. The volume is being published amid another war waged on Ukrainian soil, where the nation defends itself against an external aggressor seeking to take it over. This war has shocked the world. People are being introduced to this conflict predominantly through audiovisual media. For those who have experi- enced it, it is an inescapable, tragic reality, but for others it has become, to a large extent, a quasi-filmic spectacle which, regrettably, risks losing its gravity due to its daily presence on screens...